2018
DOI: 10.1038/s41598-018-30565-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay-Induced Multistability and Loop Formation in Neuronal Networks with Spike-Timing-Dependent Plasticity

Abstract: Spike-timing-dependent plasticity (STDP) adjusts synaptic strengths according to the precise timing of pre- and postsynaptic spike pairs. Theoretical and computational studies have revealed that STDP may contribute to the emergence of a variety of structural and dynamical states in plastic neuronal populations. In this manuscript, we show that by incorporating dendritic and axonal propagation delays in recurrent networks of oscillatory neurons, the asymptotic connectivity displays multistability, where differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 80 publications
2
49
0
Order By: Relevance
“…However, they decay exponentially quickly, and thus although these two studies differ in how far past spikes are calculated, they may be both good approximate representations of the post-synaptic events. Also, the results of the STDP model taking into account dendritic and axonal propagation delays, reported by Madadi Asl et al do not contradict ours 26 , 27 . They showed that, in both two-neuron and network motifs, high-frequency firings promote bidirectional connections, indicating a large proportion of neurons with large synaptic weights.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, they decay exponentially quickly, and thus although these two studies differ in how far past spikes are calculated, they may be both good approximate representations of the post-synaptic events. Also, the results of the STDP model taking into account dendritic and axonal propagation delays, reported by Madadi Asl et al do not contradict ours 26 , 27 . They showed that, in both two-neuron and network motifs, high-frequency firings promote bidirectional connections, indicating a large proportion of neurons with large synaptic weights.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, Madadi Asl et al revealed that STDP model incorporating dendritic and axonal propagation delay can adequately explain the existence of recurrent connections between pairs of neurons in the cerebral cortex 26 . They found that the firing frequency plays an essential role in the formation of connectivity patterns in Two-Neuron Motif 27 . Moreover, firing variability, as well as the statistical properties of the spike frequency, seems essential for real-time information processing 28 .…”
Section: Introductionmentioning
confidence: 99%
“…where A + ( A − ) and τ + (τ − ) are the learning rate and the effective time window of synaptic potentiation (depression), respectively, and sgn(Δ t ′) is the sign function. Δ t ′ = Δ t +ξ is the effective delayed time lag between pre- and postsynaptic spikes at the synaptic site (Madadi Asl et al, 2017, 2018a). Δ t = t post − t pre is the original time lag between pre- and postsynaptic spike pairs, and ξ = τ d − τ a is the difference between dendritic and axonal propagation delays.…”
Section: Propagation Delays: Computational Aspectsmentioning
confidence: 99%
“…By assuming that the neurons remain phase-locked, it was illustrated that the two-neuron results can be extended to recurrent networks of spiking neurons (Madadi Asl et al, 2017, 2018a). Different combinations of dendritic and axonal propagation delays can lead to the emergence of symmetric connections, i.e., either two-neuron bidirectional loops, in the case that dendritic propagation delays are greater than the axonal delays (Figure 2A), or loosely connected motifs when axonal propagation delays are greater than the dendritic delays (Figure 2C) (Madadi Asl et al, 2017).…”
Section: Propagation Delays: Computational Aspectsmentioning
confidence: 99%
See 1 more Smart Citation